SOURCE OF WORKING CAPITAL - Hrynyuk, Iryna (Journal of European Economy, 2017)
The article deals with the analysis of the main sources of raising additional funds, the risks and liabilities associated with them to meet the requirements of current legislation of Ukraine. There has been made the conclusion about the expediency of different funding sources.